Strategies for engineering improved nitrogen use efficiency in crop plants via redistribution and recycling of organic nitrogen - Melino, Vanessa J; Tester, Mark A; Okamoto, Mamoru (Current opinion in biotechnology, 2022)
[Display omitted] •Manipulation of ureide and amino acid transporters changes whole plant distribution of nitrogen and improves NUE.•Nitrogen from macromolecules can be recycled via selective autophagy pathways with greatest benefits under N stress.•Targeting alleles regulating plant responses to nitrogen may improve grain protein content. Global use of nitrogen (N) fertilizers has increased sevenfold from 1960 to 1995 but much of the N applied is lost to the environment. Modifying the temporal and spatial distribution of organic N within the plant can lead to improved grain yield and/or grain protein content for the same or reduced N fertilizer inputs. Biotechnological approaches to modify whole plant distribution of amino acids and ureides has proven successful in several crop species. Manipulating selective autophagy pathways in crops has also improved N remobilization efficiency to sink tissues whilst the contribution of ribophagy, RNA and purine catabolism to N recycling in crops is still too early to foretell. Improved recycling and remobilization of N must exploit N-stress responsive transcriptional regulators, N-sensing or phloem-localized promotors and genetic variation for N-responsive traits.